2021
DOI: 10.3390/polym13183036
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Synthesis, Properties, and Applications of Polylactic Acid/Silica Composites

Abstract: Polylactic acid (PLA)/silica composites as multifunctional high-performance materials have been extensively examined in the past few years by virtue of their outstanding properties relative to neat PLA. The fabrication methods, such as melt-mixing, sol–gel, and in situ polymerization, as well as the surface functionalization of silica, used to improve the dispersion of silica in the polymer matrix are outlined. The rheological, thermal, mechanical, and biodegradation properties of PLA/silica nanocomposites are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 97 publications
2
24
0
Order By: Relevance
“…The exposure of the studied material to the action of γ-radiation induces a diminution in the thermal stability, especially in the range of higher temperatures [ 74 ] ( Figure 3 ). The oxidation starts earlier and the temperature increases over 200 °C, which may induce the slight recombination of hydrocarbon radicals and cyclization of lactide structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exposure of the studied material to the action of γ-radiation induces a diminution in the thermal stability, especially in the range of higher temperatures [ 74 ] ( Figure 3 ). The oxidation starts earlier and the temperature increases over 200 °C, which may induce the slight recombination of hydrocarbon radicals and cyclization of lactide structures.…”
Section: Resultsmentioning
confidence: 99%
“…The nanotechnologies approaches provide the specific solutions for the formulations of resistant materials, which are based on improving the contribution of inorganic fillers [ 83 , 84 ]. Various formulations based on PLA try to find optimal solutions for the enlargement of application areas: biodegradability [ 74 , 85 , 86 ], medical range [ 87 , 88 ], packaging products [ 89 , 90 ], optical bioimaging [ 91 ], controlling the release of hydrophilic pharmaceutical compounds [ 92 ], production of contractible materials [ 93 ], recycling [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…To provide mechanical strength, PLA was selected as the loading scaffold for BG. PLA is known as a degradable polymer, the degradation product is nontoxic and has good mechanical properties ( Kaseem et al, 2021 ). The results of the study showed that the composite of the two materials not only improved the mechanical properties and elastic modulus but also met the requirements of bone induction.…”
Section: Discussionmentioning
confidence: 99%
“…PLA has good physical and rheological properties, similar to polyethylene terephthalate and polystyrene. Due to its non-toxicity, biodegradability and biocompatibility, PLA can be used in many industries as well as in medicine in biomedical applications [23][24][25].…”
Section: Materials Chemical Compositionmentioning
confidence: 99%